Small Tropical Abalone (Haliotis squamata Reeve, 1846) in Indonesia: Current Research Status and Future Prospect - Permana, I Gusti Ngurah; Gustiano, Rudhy; Chodriyah, Umi; Ahmad, Riza Zainuddin; Kusmini, Irin Iriana; Lukman, Lukman; Yosmaniar, Yosmaniar; Kadarini, Tutik; Kurniasih, Titin; Murdinah, Murdinah (Zuriat, 2024)
Abalone farming is gaining popularity worldwide as demand grows. The importance of abalone farming throughout Indonesia is due in part to expanding demand for both local and foreign abalone, and to a growing awareness of the necessity for sustainable seafood production. This study relies on fourty-six scientific papers published between 2000 and 2023. The distribution and variety, bio-reproduction and breeding, growth, and commerce of small tropical abalones are carefully explored to highlight the current research state, as well as the opportunities and challenges in the existing abalone sector. Finally, all interactions yield findings that can be utilized to guide government policy. To realize its full potential, the Indonesian abalone industry must overcome difficulties such as competition and price fluctuations. Key goals include developing sustainability collection and trading methods, reliably supplying high-quality abalone goods, and expanding their reach through global trade. Addressing these challenges will enable the Indonesian abalone industry to thrive in the next years. The abalone business in Indonesia has a long history, is now growing and active, and presents significant potential. With ongoing R&D investments, the Indonesian abalone sector can meet national and global market demands while being sustainable. Understanding the current situation of abalone research in Indonesia is critical to maintaining the industry's long-term survival.